First records of aquatic Heteroptera from Friuli-Venezia Giulia (Italy) - Cianferoni, Fabio (Acta entomologica slovenica (Ljubljana), 2015)
Two species of aquatic Heteroptera are recorded for Friuli-Venezia Giulia (Italy) for the first time: Anisops sardeus sardeus Herrich-Schäffer, 1849 (Nepomorpha, Notonectidae) and Gerris (Gerris) argentatus Schummel, 1832 (Gerromorpha, Gerridae). Remarks on their general distribution are also given.
Keywords: Anisops sardeus; first records; Gerris argentatus; Gerromorpha; Heteroptera; Italia; Italija; Italy; Nepomorpha; Notonectidae; prvi podatki; stenice